PERAN FINANCING TO DEPOSIT RATIO, CAPITAL ADEQUACY RATIO DAN NON PERFORMING FINANCING TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA - Widodo, Dheevanadea Arnetta; Usman, Usman; Oktavia, Vicky; Safitri, Maria (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: Indonesia's Islamic financial sector has grown quickly, mostly as a result of Islamic banking's contribution to economic growth through fund intermediation. However, a several problems, result in lower profitability for Islamic institutions, especially during the COVID-19 pandemic. This study aims to investigate the effects of the Financing Deposit Ratio (FDR), Non-Performing Financing (NPF), and Capital Adequacy Ratio (CAR) on Return on Assets (ROA), a metric used to quantify profitability.Methods: The methodology used is quantitative causal analysis with multiple linear regression techniques. All Islamic Commercial Banks (BUS) that are registered with the Financial Services Authority (OJK) make up the study population; 11 banks were selected by selective sampling utilising 2019–2023 data.Results: The study's findings indicate that ROA is significantly impacted positively by FDR and CAR and negatively by NPF. This shows that effective financing and capital adequacy increase profitability, while problematic financing decreases it.In conclusion, liquidity management, capitalization, and financing quality are very important to maintain the financial performance of Islamic banks. Management is advised to strengthen the risk management system and improve operational efficiency.